Averting Catastrophes: The Strange Economics of Scylla and Charybdis - Martin, Ian W. R.; Pindyck, Robert S. (American Economic Review, 2015)
Faced with numerous potential catastrophes—nuclear and bioterrorism, mega-viruses, climate change, and others—which should society attempt to avert? A policy to avert one catastrophe considered in isolation might be evaluated in cost-benefit terms. But because society faces multiple catastrophes, simple cost-benefit analysis fails: even if the benefit of averting each one exceeds the cost, we should not necessarily avert them all. We explore the policy interdependence of catastrophic events, and develop a rule for determining which catastrophes should be averted and which should not. (JEL D61, Q51, Q54)